The position of Victory Point, King William Island - Cyriax, R. J. (Polar Record, 1952)
The narratives of the explorers who have visited the north-west coast of King William Island, and some of the maps, do not agree concerning the position of Victory Point, where, in the opinion of most writers, Captain F. R. M. Crozier, R.N., landed and left a record in April 1848 after abandoning H.M. ships Erebus and Terror . Since a complete survey of the locality is only a question of time, it may be useful to put on record the present knowledge of the subject.